Secondary succession and soil nutrient dynamics in abandoned fallows of goth in Panchase, central midhill, Nepal - Pathak, Hom Nath; Bhuju, Dinesh Raj (Journal of Natural History Museum, 2018)
Livestock farming in Nepal have a common feature of temporary shelter called goth. In recent years, young people in the villages go for foreign jobs and there is severe lack of labour force and the Gothpractice has gradually been abandoned. In the abandoned got fallows, plant succession is observed. In Panchase, abandoned fallows of one year, two years, five years, 15 years were sampled. The sampling included species-wise count of plants and their coverage. Density, frequency and coverage were determined to obtain species diversity. Soil samples were taken from each of the fallow studied. It was found that the species diversity increased with the age of the fallow land, while beta diversity decreased with the successive fallow age. Soil samples were analyzed for pH value, organic matter, water holding capacity, nitrogen, phosphorus and potassium value. Aluminum and phosphorus were the determinants in succession of herbs by shrubs and then by tree species to climax.